Perfil epidemiológico de portadores de hepatite C notificados em hospitais de referência em Fortaleza, Ceará - Chao, Otto Wen Hae (2014)
Hepatitis C is considered a serious public health problem, generating consequences for the health of their patients. The objective of this study is to evaluate the epidemiological profile of patients with hepatitis C reported at referral hospitals in Fortaleza. It is a descriptive, retrospective, cross-sectional study with a quantitative approach. Data collection occurred between January 2008 and December 2012 through the SINAN record, and they are entered and tabulated with Excel 2010. Were then exported and entered into SPSS 16.0 for analysis and interpretation. Demographic and epidemiological variables were described in the study. As to results, it is envisaged that between 2008 and 2012, 464 cases were reported, 68.8% (319) in HSJ and 31.2% (145) in HUWC, the year of 2010 had the highest incidence with 26.6% (123), 2012 with 23.5% (109), 2009 with 19.4% (90), 2011 with 16.4% (76) and 2008 with 14.1% (66). When distributed by gender, males have 62.9% (292), and females 37.1% (172). With regard to the county of residence of the patients reported, 68.5% (318) are from Fortaleza, 17.0% (79) within the state of Ceará, 10.6% (49) correspond to the municipalities within the metropolitan region of Fortaleza (RMF) and 3.9% (18) from other states of Brazil. Distribution relative to age, with an average of 47.94 years old and a median of 48.00 and standard deviation of 12,559, ranging from a minimum of 18 and maximum of 88 years old, have the highest incidence above 50 years of age with 44.0% (204), 41-50 years with 28.9% (130), 31 to 40 years with 18.1% (84), 21 to 30 years with 8.6% (40) and under 20 years of age with 1.2% (6). With respect to the variable probable source of infection, there was a high number (ranging from 53% to 62.3%) of cases ignored. With respect to diagnostic classification, was obtained 98.7% (458) chronic and 1.3% (6) Acute. The most frequently observed genotype was type 1 with 51.3% (238), followed by type 3 with 21.8% (101). Conclusion: Emphasizes the importance of filling the completion of all fields of epidemiological form of investigating cases of viral hepatitis.